The vanishing year : a novel - Moretti, Kate (New York : Atria Books, 2016)
""The Vanishing Year is a stunner. A perfectly compulsive read that's impossible to put down." -Mary Kubica. "A chilling, powerful tale of nerve-shattering suspense." -Heather Gudenkauf. Zoe Whittaker is living a charmed life. She is the beautiful young wife to handsome, charming Wall Street tycoon Henry Whittaker. She is a member of Manhattan's social elite. She is on the board of one of the city's most prestigious philanthropic organizations. She has a perfect Tribeca penthouse in the city and a gorgeous lake house in the country. The finest wine, the most up-to-date fashion, and the most luxurious vacations are all at her fingertips. What no one knows is that five years ago, Zoe's life was in danger. Back then, Zoe wasn't Zoe at all. Now her secrets are coming back to haunt her. As the past and present collide, Zoe must decide who she can trust before she--whoever she is--vanishes completely. A "dark, twisty, edge-of-your-seat suspense" (Karen Robards), The Vanishing Year combines the classic sophistication of Ruth Rendell and A.S.A. Harrison with the thoroughly modern flair of Jessica Knoll. Told from the point-of-view of a heroine who is as relatable as she is enigmatic, The Vanishing Year is an unforgettable new novel by a rising star of the genre"--
Keywords: Upper class women -- Fiction; Secrecy -- Fiction; Identity (Psychology) -- Fiction; FICTION / Suspense; FICTION / Romance / Suspense; FICTION / Contemporary Women; California -- Fiction; New York (N.Y.) -- Fiction; Romantic suspense fiction; Mystery fiction; Psychological fiction